Analisis Manajemen Pelayanan Gizi di Rumah Sakit Jiwa Grhasia Daerah Istimewa Yogyakarta - Muliawardani, Rizki; Mudayana, Ahmad Ahid (Universitas Ahmad Dahlan, 2016)
Background: Management of nutrition service was needed by a hospital management because the more difficult in achieving a good customer services including patients. The problems of nutrition services in hospital had lack of quantity and quality of nutrionist and staffs. The aimed of this research to evaluate the nutrition of department system. Method: This study was a descriptive research with qualitatif approach. The subjects were the chief medical support, the head of hospital nutrition department, nutritionists, and staff of nutrisionist. The tool of this study was indepth interview method. The data analysis used content analysis. Results: The research showed that nutrition care planning had been implemented and according to thenutrition departments in hospital, the organization was in good order, the implementation of nutrition services had been going well and according to the nutrition departments in hospital but care activities has not run regularly, supervision has been going well, and evaluation has been going well. Conclusion: The implementation of nutrition services in hospital had a good of management system, while the lack of planning and services were identified.